Pelatihan Metode Jibril untuk Meningkatkan Kefasihan Membaca Al-Qur’an di TPQ Achsin Qifly, Besuk Agung Kraksaan - Sulusiyah, Sulusiyah; Sugiono; Nur Hidayati; Diana Safitri; Nilam Nastiti Normala Dewi (Yayasan Literasi Altruis Khatulistiwa, 2025)
This community service program was motivated by the low level of Qur’anic reading fluency among students at TPQ Achsin Qifly, Besuk Agung. A preliminary survey revealed that approximately 50% of the students were unable to read the Qur’an fluently and in accordance with proper tajwid rules. This condition was primarily caused by the use of conventional teaching methods and the lack of participatory approaches. The purpose of this program was to improve the students’ Qur’anic reading skills through the implementation of the Jibril Method, which consists of three main components: talaqqi (direct recitation), takrir (repetition), and tas-hih (correction). The program employed a qualitative case study approach combined with participatory methods, actively involving students in all stages of the learning process, from needs assessment to evaluation. The results demonstrated significant improvements in the students’ pronunciation (makhraj), application of tajwid rules, and reading fluency. In addition to technical skill enhancement, this program also fostered positive changes in students’ learning behavior and increased parental involvement in supporting the learning process. Therefore, the Jibril Method has proven to be effective and suitable as a holistic and adaptive approach to meet the students’ needs. However, these findings are still contextual, and further research is required to explore its applicability in other Qur’anic learning centers.